Two new chemical constituents from the rhizomes of Actaea dahurica. Issue 7 (3rd April 2022) - Ma, Sen-Ju; Li, Hai-Bo; Shao, Jun-Ran; Pang, Qian-Qian; Li, Ting; Yao, Xin-Sheng; Yu, Yang
Abstract: A new phenylpropanoid allopyranoside (1 ) and a new indolinone alkaloid (2 ) were isolated from the rhizomes of Actaea dahurica (syn. Cimicifuga dahurica ). The structures of those two compounds were deduced as cimicifugaside F (1 ) and 3 E, 11 E -(3-methyl-2-butenylidene acid)-2-indolinone-1- O - β -d -glucopyranoside (2 ) by detailed analysis of their MS, 1D and 2D NMR data and comparison with literatures. Additionally, the isolates were evaluated for their inhibitory effects on the production of NO by LPS-stimulated RAW 264.7 macrophages. Graphical Abstract: